How affection leads to overall brand equity and brand awareness? The mediating role of activation - Burhanudin, Burhanudin; Waluyo, Ananda Putri (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2023)
The food and beverage industry is a sector that deals with highly demanded products. The aim of this study is to examine how the presence of affection influences activation and further, both the overall brand equity and brand awareness. In addition, this study examines activation acting as a mediation factor in the relationship between affection and overall brand equity as well as between affection and brand awareness. There were 202 respondents who had purchased Excelso products participating in this study. The data was analyzed with a structural equation modeling. The findings of this research show affection influences activation and, further, both overall brand equity and brand awareness. In addition, activation mediates the relationship between affection and overall brand equity and between affection and brand awareness